An on-line capacitor state identification method based on improved RLS. Issue 3 (1st July 2021) - Cheng, Shu; Liu, Chang; Xue, Shengxian; Wang, Maoyu; Wu, Xun; Luo, Yu
Abstract: As an essential part of DC-Link in the power converter, capacitor plays a crucial role in absorbing ripple current and suppressing ripple voltage. The health and residual service life of the DC-Link capacitor is one of the decisive factors for the safety, stability, and efficiency of the system in which it is located. Aiming at the shortcomings of existing methods, such as low dynamic sensitivity of data update and fluctuation of identification results, a capacitor state identification method based on improved RLS is proposed in this paper. The proposed method is optimized by introducing the forgetting factor algorithm and root means square algorithm to modify the iterative formula and final identification results. Compared with existing methods, this method can identify the capacitor's current state in real time and accurately. Finally, we successfully verified the accuracy, robustness, and adaptability of the proposed method by a series of experimental tests on a dSPACE platform.